Study of oscillations and pattern formation in the CO + O2 reaction on Pt(1 0 0) surfaces through dynamic Monte Carlo simulation - Zgrablich, Jorge Andres (2007)
Oscillations and pattern formation driven by a surface reconstruction are studied for the catalytic oxidation of CO on Pt(1 0 0) single-crystal surfaces through dynamic Monte Carlo simulations at low pressure and relatively high temperatures conditions. Sustained, modulated, irregular and damped oscillations are observed in our analysis as well as the formation of cellular, target, double spiral, spiral wave and turbulent patterns. The effect and the importance of the hex ⇆ 1 X 1 surface phase transition and partial pressure of the reactants in the gas phase on the behavior of the system are discussed.